Primary Plasma Cell Leukaemia (pPCL) Pada Sumsum Tulang Belakang: Laporan Kasus dan Tinjauannya - Indah Afriwanty Simatupang; Fahmi Irsan Nasution; Hendri Meirialdi (Jurnal Siti Rufaidah, 2025)
Plasma Cell Leukemia (PCL) is a rare lymphoproliferative disorder characterized by the proliferation of malignant plasma cells in the bone marrow and their presence in the peripheral blood. PCL is classified into primary plasma cell leukemia (pPCL), which occurs de novo without a prior history of multiple myeloma, and secondary plasma cell leukemia (sPCL), which arises in association with relapsed or refractory multiple myeloma. A 58-year-old woman presented with right hip pain that had been ongoing for four months. The pain progressively worsened, limiting her ability to move her leg and eventually causing significant difficulty in walking. She also experienced bilateral lower limb weakness and an unintentional weight loss of 10 kg over the same period. The patient denied any history of trauma. Physical examination revealed pallor without signs of bruising or spontaneous bleeding. Laboratory findings showed severe anemia (Hb 6.5 g/dL), leukocytosis (24,100/µL), thrombocytopenia, an elevated erythrocyte sedimentation rate, and 25% plasma cells on peripheral blood smear. Bone marrow aspiration demonstrated 40% infiltration by plasma cells. Based on the patient’s clinical presentation, physical examination, and laboratory findings, the diagnosis is consistent with primary Plasma Cell Leukemia.